2008
DOI: 10.1007/s10549-008-0191-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of 70-gene prognosis signature in node-negative breast cancer

Abstract: International audienceThe 70-gene prognosis signature (van't Veer et al., Nature 415(6871):530–536, 2002) may improve the selection of lymph node-negative breast cancer patients for adjuvant systemic therapy. Optimal validation of prognostic classifiers is of great importance and we therefore wished to evaluate the prognostic value of the 70-gene prognosis signature in a series of relatively recently diagnosed lymph node negative breast cancer patients. We evaluated the 70-gene prognosis signature in an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 37 publications
3
97
1
3
Order By: Relevance
“…The prognostic value of 70-gene profile has been validated in a range of series of patients [3][4][5][6]. These studies confirmed that the 70-gene signature accurately discriminates between patients at high risk of distant metastasis and death and patients with a favorable prognosis.…”
Section: Introductionmentioning
confidence: 64%
“…The prognostic value of 70-gene profile has been validated in a range of series of patients [3][4][5][6]. These studies confirmed that the 70-gene signature accurately discriminates between patients at high risk of distant metastasis and death and patients with a favorable prognosis.…”
Section: Introductionmentioning
confidence: 64%
“…8,13,[22][23][24][25] Evidence supporting the predictive value of the 70-GS on CT benefit is limited; therefore, its clinical utility mainly lies in its prognostic capacity. [26][27][28] Currently, the MINDACT trial is being conducted and the first results are expected by the end of this calendar year, which will further assess the predictive capacity of the 70-GS in a randomized prospective setting.…”
Section: Discussionmentioning
confidence: 99%
“…The 70-gene signature, which is being performed on fresh (frozen) tumor tissue, has shown to have a strong prognostic power for early breast cancer patients [5,6,13,14]. The 70-gene set was developed using the so-called data-driven approach, i.e., without a priori knowledge of the role of the involved genes, whereas for example the 21-gene RS used the knowledge-driven approach, i.e., genes known to be involved in breast cancer formation and metastatic spreading were included.…”
Section: Introductionmentioning
confidence: 99%